EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SCIENTIFIC PADA MATERI FUNGSI DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI DI KABUPATEN KARANGANYAR - Hendry Putra; Budiyono Budiyono; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the effect of learning model (LM) toward learning outcomes (LO) in mathematics viewed from the learning styles (LS). The learning models of this research were cooperative LM of the NHT with Scientific, the cooperative LM of the TPS with Scientific, and the classical learning with Scientific. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Karanganyar. The instruments used to gather the data were test of LO in Mathematics and questionnaire of LS. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows: 1) the students instructed NHT had a better LO in Mathematics than those instructed TPS and those instructed the classical learning. Furthermore, the students instructed TPS had a better LO in Mathematics than those instructed the classical learning. 2) the LO in Mathematics of the students with the auditory LS was better than that of the students with the visual LS and that of the students with the kinesthetic LS. In addition, the LO in Mathematics of the students with the visual LS was better than that of the students with the kinesthetic LS. 3) on model of the NHT, the students with the visual LS had the same LO in Mathematics as the students with the auditory LS. Moreover, the students with the visual and auditory LS had a better LO in Mathematics than those the students with the kinesthetic LS. On model of the TPS and the classical learning results in the same LO in each of LS. 4) the students with the visual and auditory LS, NHT and the classical learning results in the same LO in Mathematics as TPS. Furthermore, NHT results in a better LO in Mathematics than the classical learning. The students with the kinesthetic LS had the same LO in each of LM.Keywords: NHT with Scientific, TPS with Scientific, learning outcomes, learning styles.